Features of the activities of executive government bodies with authorities in the field of construction in Ukraine - Matseliukh, Ivanna; Radyshevska, Olesya; Artemenko, Olena V.; Lisohor, Yurii (P.A. Persona e Amministrazione, 2023)
The purpose of the article is a comprehensive analysis of the main aspects of the activities of executive authorities in the field of construction. In order to carry out a full-fledged analysis of the main aspects of the activities of the executive authorities in the field of construction, a complex of general scientific, special and legal methods was used, which ultimately allowed the authors to form relevant conclusions and proposals. It has been proven that the concept of subjects of permitting activity in the field of urban planning covers primarily subjects of legal relations, the object of which is the issuance of a permit document. On the other hand, the subject of urban planning activity (individual or legal entity) participates in such legal relations. The authors consider such a concept of the subjects of the specified legal relations to be narrow, since the specified legal relations constitute only one element of the system of legal relations, thanks to which the permission activity is carried out. It was concluded that the current state of administrative and legal regulation of the permit system is characterized by a gradual weakening of bureaucratic procedures by public administration entities, and this, in turn, contributes to the reduction of manifestations of corruption in the field of construction. The results of this study can be used for further analysis of the entire urban planning system in the context of administrative and legal regulation, as well as for revision by the legislative body in the process of making changes to the current legislation.